On grain boundary segregation in molybdenum materials. (5th December 2017) - Leitner (née Babinsky), K.; Felfer, P.J.; Holec, D.; Cairney, J.; Knabl, W.; Lorich, A.; Clemens, H.; Primig, S.
Abstract: The character and distribution of grain boundaries (GBs) in molybdenum materials and their decoration with solutes may lead to strengthening or weakening effects which limits the structural application of Mo, especially in the recrystallized state, as as-deformed materials usually exhibit transgranular failure. Investigations of the structure and chemistry of GBs in Mo materials at the nanoscale are required to answer longstanding questions around their fracture behavior. We present a detailed investigation of segregation at a total of 22 high-angle GBs in Mo materials in their as-deformed and recrystallized states. We reveal the full crystallographic and chemical character of each individual GB by combining transmission Kikuchi diffraction and atom probe microscopy. We demonstrate that the detrimental elements P, N, and O segregate to all random high angle GBs. On the other hand, C—which has a strengthening effect—was only found at low-Σ GBs in recrystallized materials. We support these experimental observations by first principle calculations. Our results provide an advance on grain boundary segregation engineering in these important technological materials. Graphical abstract: Highlights: Atom probe reveals crystallography and chemistry of 22 grain boundaries (GBs) in as-deformed & recrystallized Mo. As-deformed Mo exhibits P, N, and O grain boundary segregation with interfacial excess (IFE) between 0.05 – 2 atoms/nm 2 . After recrystallization, higher IFE (double IFE at 32° rotation angle) but no correlation between IFE and rotation angle. Significant C segregation to low-sigma GBs in the recrystallized state as supported by first principles calculations.